1983
DOI: 10.1017/s0022112083003250
|View full text |Cite
|
Sign up to set email alerts
|

Flow between rotating disks. Part 1. Basic flow

Abstract: Laser-Doppler velocity measurements were obtained in water between finite rotating disks, with and without throughflow, in four cases: ω1 = ω2 = 0; ω2/ω1 = −1; ω2/ω1 = 0; ω2/ω1 = 1. The equilibrium flows are unique, and at mid-radius they show a high degree of independence from boundary conditions in r. With one disk rotating and the other stationary, this mid-radius ‘limiting flow’ is recognized as the Batchelor profile of infinite-disk theory. Other profiles, predicted by this theory to coexist with the Batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 20 publications
2
20
0
1
Order By: Relevance
“…The value of the core swirl ratio is not universal: Owen and Rogers [11] found a theoretical value equal to 0.382 in the case of infinite disks, Szeri and al. [15] obtained 0.313 in a system rotor-stator with a large clearance, this last result being also obtained by Dijkstra and van Heijst [16]. When the cavity is opened to the atmosphere at the periphery, D'Haudt [17] showed that the peripheral layout of the system has a strong influence on the flow properties in the case of an isolated cavity.…”
Section: Introductionmentioning
confidence: 60%
“…The value of the core swirl ratio is not universal: Owen and Rogers [11] found a theoretical value equal to 0.382 in the case of infinite disks, Szeri and al. [15] obtained 0.313 in a system rotor-stator with a large clearance, this last result being also obtained by Dijkstra and van Heijst [16]. When the cavity is opened to the atmosphere at the periphery, D'Haudt [17] showed that the peripheral layout of the system has a strong influence on the flow properties in the case of an isolated cavity.…”
Section: Introductionmentioning
confidence: 60%
“…This recirculation pattern has Ž . been observed in laminar flow by Szeri et al 1983 , using laser Doppler anemometry. The permeate flux is larger for Ž .…”
Section: Effect Of Inletr R R R Routlet Configurations On Module Perfmentioning
confidence: 99%
“…To further validate the numerical solution, a sample problem is created and compared against experimental results obtained by Szeri et al (1983). Szeri et al obtained Laser-Doppler velocity measurement in water between finite rotating disks.…”
Section: Validation Of the Modelmentioning
confidence: 99%